2012
DOI: 10.1159/000338831
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for JAK2<sup>V617F</sup> Mutation in Monoclonal B Cells in 2 Patients with Polycythaemia Vera and Concurrent Monoclonal B Cell Disorder

Abstract: Occurrence of Philadelphia chromosome-negative myeloproliferative neoplasms (Ph MPN) and lymphoproliferative disorders, like B cell chronic lymphocytic leukaemia (B-CLL), in the same patient is rare. JAK2V617F mutation was recently introduced as a powerful diagnostic tool for Ph MPN. JAK2V617F mutation is not present in B-CLL. In 4 previously reported patients with JAK2V617F-positive Ph MPN and B-CLL there was no definitive proof of JAK2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
(29 reference statements)
0
11
1
Order By: Relevance
“…Interestingly, cytoreductive treatment for MPN had no impact on lymphoid cells counts and reciprocally [6]. In subsequent studies, authors showed that cells of myeloid and Blymphoid diseases did not harbor common mutations [7]. Of note, to the best of our knowledge, this is the first report of an association between a mutation of the exon 12 of JAK2 and a CLL.…”
Section: Casementioning
confidence: 86%
“…Interestingly, cytoreductive treatment for MPN had no impact on lymphoid cells counts and reciprocally [6]. In subsequent studies, authors showed that cells of myeloid and Blymphoid diseases did not harbor common mutations [7]. Of note, to the best of our knowledge, this is the first report of an association between a mutation of the exon 12 of JAK2 and a CLL.…”
Section: Casementioning
confidence: 86%
“…Of the 28 cases of JAK2 V617F-positive B-CLL patients reported in the literature (Table 1) (615), the male and female ratio was 1.6:1 (17 males vs. 11 females), the median age of the males was 69 years (range, 55–94 years) and was 74 years (range, 58–82 years) for the females. In total, 27 patients exhibited coexistent Ph-MPN (essential thrombocythemia, n=16; polycythemia vera, n=10; and idiopathic myelofibrosis, n=1).…”
Section: Discussionmentioning
confidence: 99%
“…This mutation has also been identified in a small number of other myeloid malignancies (2,3), however, rarely presents in lymphoid malignancies (4,5). Following a search of the English language literature between 2006 and January 2013 using the search terms ‘B-cell lymphocytic leukemia’ (B-CLL) and ‘JAK2’, 28 JAK2 V617F-positive B-CLL patients were identified (615). All of these patients exhibited a Ph-MPN concomitantly.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time also CD20 + /CD5 -B cells, T cells and NK were found JAK2V617F positive while the mutation was not detected in the CD20 + /CD5 + B cells. On the base of these results, the author concludes that there is no evidence that the proliferative behavior of B cells is mediated by the JAK2V617F mutation even if the B-CLL and the JAK2V617F-positive MPN do coexist [64]. On the contrary, Kodali et al reported a case of one patient who had both a JAK2-mutated MPN and B-CLL and studied the status of the mutation in stem cells, myeloid and lymphoid cell lines.…”
Section: The Role Of Jak2 In Lymphomasmentioning
confidence: 99%
“…Negative in CD5+ B lymphocytes PV [64] 3 Negative PV [63] 1 Negative ET The clinical and hematologic data refer to the time when the peripheral blood was collected and analyzed for the JAK2V617F mutation. B-CLL: B-cell chronic lymphocytic leukemia; M: Male.…”
mentioning
confidence: 99%